Ecotone shift and major droughts during the mid-late holocene in the central Tibetan Plateau - Shen, Caiming; Liu, Kam-Biu; Morrill, Carrie; Overpeck, Jonathan T.; Peng, Jinlan (彭金兰); Tang, Lingyu (唐领余) (ECOLOGICAL SOC AMER, 2008)
A well-dated pollen record from a large lake located on the meadow-steppe ecotone provides a history of ecotone shift in response to monsoonal climate changes over the last 6000 years in the central Tibetan Plateau. The pollen record indicates that the ecotone shifted eastward during 6000-4900, 4400-3900, and 2800-1600 cal. yr BP when steppes occupied this region, whereas it shifted westward during the other intervals when the steppes were replaced by meadows. The quantitative reconstruction of paleoclimate derived from the pollen record shows that monsoon precipitation fluctuated around the present level over the last 6000 years in the central Tibetan Plateau. Three major drought episodes of 5600-4900, 4400-3900, and 2800-2400 cal. yr BP are detected by pollen signals and lake sediments. Comparison of our record with other climatic proxy data from the Tibetan Plateau and other monsoonal regions shows that these episodes are three major centennial-scale monsoon weakening events.